Public Pension Fund Structure And Mechanisms: A Case Study Of The Tanzanian Pension Funds System - Zubeda Chande Mpinga; Wim Westerman (The Central European Review of Economics and Management (CEREM), 2017)
Good governance structures have become an issue of public interest, including public pension systems. This study assesses the pension funds governance in Tanzania, with a special focus on board of trustees' issues. The growing interest referred to, is partly because the quality and performance of the funds trustees determines the income flows to which members are entitled and promised, as well as any shortfalls thereof, that may require interventions. Our findings suggest that board of trustees play an important role for funds governance and hence performance. The pension fund structure and mechanisms in Tanzania uphold high standards. Yet, a major issue is that the board selection seems to be politically motivated and that the government claims most board seats, making conflicts of interest likely to occur repeatedly.
Keywords: 330